A new approach to biostratigraphy in the Karoo retroarc foreland system: Utilising restricted-range palynomorphs and their first appearance datums for correlation. (April 2018) - Barbolini, Natasha; Rubidge, Bruce; Bamford, Marion K.
Abstract: The main Karoo Basin (MKB), internationally renowned for its wealth of fossil tetrapods, has been lithostratigraphically subdivided into three discrete regions: two (east and west) proximal facies adjacent to the Cape Fold Belt, and a distal facies, away from the Cape Fold Belt. Because of lithological differences between formations of the proximal and distal sectors of the MKB, it has been difficult to correlate time-equivalent lithostratigraphic units in the different sectors. Palynology provides a tool for refining stratigraphic correlations within the MKB, but only species with restricted ranges are biostratigraphically significant. Restricted-range palynomorph taxa from the Ecca and Beaufort groups indicate the following relationships: the lowermost Vryheid Formation palynoflora can be strongly correlated with that of the Prince Albert Formation, whereas the Whitehill–Collingham formations and No. 2 seam (Vryheid Formation), and the Ripon Formation and No. 4 seam (Vryheid Formation) can be tentatively linked using palynology. The lower–middle Normandien Formation in the north is chronologically equivalent to the Ripplemead member of the Balfour Formation in the south. Although the Ecca–Beaufort Group boundary is known to be diachronous, restricted-range palynomorphs cannot yet confirm that the uppermost Ecca Group in the northern part of the basin was deposited at the same time as the lower Beaufort Group in the south. This study demonstrates that despite diachronous ranges of some taxa, palynology is useful in correlating age-equivalent lithostratigraphic units in the proximal and distal sectors of the basin. A new First Appearance Datum (FAD) palynozonation for the Karoo is presented that is calibrated by the most recent radiometric dates for South Africa, Australia, and South America. The new zones are also correlated with Permian successions in Antarctica, Zambia, Botswana, and India. Future palynostratigraphic work in South Africa must take into account the ranges and FADs of these palynomorph taxa in order to make meaningful biostratigraphic correlations in the Karoo Basin and across Gondwana. Graphical abstract: Highlights: We revise previous palynological work in the main Karoo Basin of South Africa. Restricted-range palynomorphs correlate basinwide Permian lithostratigraphic units. A new palynozonation for South Africa is calibrated by the latest radiometric dates.